Review of the concept of response cost as effort or physical force in the Brazilian literature (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The present study investigated whether researches that defines response cost, as mentioned above, uses references to define it and if they use the same definition of the concept. The terms "custo da resposta" and "custo de resposta" were searched in CAPES thesis and dissertation database and in seven journals with frequent publications of behavior analysts. We found 104 results, of which 12 defined the response cost as physical effort or physical force. The results were: (1) in nine articles, it was cited references that use effort without using the term response cost; (2) in one, there were references that used the term response cost without mentioning effort; (3) in other one there was some references that used response cost as physical effort or physical force and this paper was the only one that presented a congruent bibliographic basis of this term.
Keywords: physical cost; physical effort; physical force; response cost; response effort